2015
DOI: 10.1021/acs.jpcb.5b07365
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effect of (LK)nL Peptides on the Onset of Insulin Amyloid Fiber Formation at Hydrophobic Surfaces

Abstract: Soluble proteins are constantly in contact with material or cellular surfaces, which can trigger their aggregation and therefore have a serious impact on the development of stable therapeutic proteins. In contact with hydrophobic material surfaces, human insulin aggregates readily into amyloid fibers. The kinetics of this aggregation can be accelerated by small peptides, forming stable beta-sheets on hydrophobic surfaces. Using a series of (LK)nL peptides with varying length, we show that these peptides, at lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…It reveals that the increased hydrophobicity brought by G33V mutation alters the associations between other residues and also interferes with the MC-MC interaction. Too much hydrophobic interaction is reported to have a negative effect on the protein stability as well as the formation of an aggregative nucleus in peptides-hydrophobic surface system [ 70 ], or to reduce the β-sheet content of fibrils and lead to disordered oligomers in Aβ 16–22 -crowder system [ 71 ]. In a previous REMD simulation study of G33I mutant Aβ 29–42 dimer, the enhanced hydrophobic at G33 was also reported to reduce intermolecular interaction in WT dimer [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…It reveals that the increased hydrophobicity brought by G33V mutation alters the associations between other residues and also interferes with the MC-MC interaction. Too much hydrophobic interaction is reported to have a negative effect on the protein stability as well as the formation of an aggregative nucleus in peptides-hydrophobic surface system [ 70 ], or to reduce the β-sheet content of fibrils and lead to disordered oligomers in Aβ 16–22 -crowder system [ 71 ]. In a previous REMD simulation study of G33I mutant Aβ 29–42 dimer, the enhanced hydrophobic at G33 was also reported to reduce intermolecular interaction in WT dimer [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have gone a step further to investigate mechanisms of LK peptide aggregation 12−14 and complex/film formation at interfaces. 5,15 Surprisingly fewer experimental studies have focused on the kinetic 16 or thermodynamic aspects of LK peptide adsorption. Thermodynamic analyses are important because they can provide key mechanistic insights into protein self-assembly on surfaces and the basis of protein function and stability in general.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A great number of experimental studies employing a wide variety of techniques such as solid-state nuclear magnetic resonance (ssNMR), near-edge X-ray adsorption fine structure (NEXAFS), , sum frequency generation (SFG), X-ray photoelectron spectroscopy (XPS), and time-of-flight secondary ion mass spectrometry (ToF-SIMS) have been performed on systems of LK peptides adsorbed to solid surfaces, many with SAM surfaces specifically, to determine the interfacial conformations and orientations of the adsorbed peptides. Some studies have gone a step further to investigate mechanisms of LK peptide aggregation and complex/film formation at interfaces. , Surprisingly fewer experimental studies have focused on the kinetic or thermodynamic aspects of LK peptide adsorption. Thermodynamic analyses are important because they can provide key mechanistic insights into protein self-assembly on surfaces and the basis of protein function and stability in general .…”
Section: Introductionmentioning
confidence: 99%
“…This lag phase can be dramatically shortened in the presence of substoichiometric amounts of aggregative peptides (LK9) in solution. 119 Figure 4(c) shows that this acceleration goes in pair with the rapid formation of numerous surface-adsorbed nuclei which are absent when peptide [ Fig. 4(a)] or insulin [ Fig.…”
Section: H Atomic Force Microscopymentioning
confidence: 99%